Four new species of leafhopper genus Bhatia Distant (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from southern China with an updated checklist and key to Chinese fauna - Qu, Ling; Yang, Yan-Qiong; Yu, Zhou; Dai, Ren-Huai (Zootaxa, 2025)
Four new species of the leafhopper genus Bhatia Distant are described and illustrated from southern China, Bhatia bilateritra sp. nov. (Hainan Province), B. furcata sp. nov. (Yunnan Province), B. holodonta sp. nov. (Yunnan Province) and B. affinikoreana sp. nov. (Hainan Province). All type specimens are deposited in Institute of Entomology of Guizhou University (GUGC). Detailed morphological descriptions, diagnostic characters, and illustrations are provided for each species. Additionally, a comprehensive checklist of all known Bhatia species from China is presented, along with an updated key for their identification.